Overview of Chatbot Usage on Mental Health: A Scoping Review - Permatasari, Ririn Indah; Artha, Dian Parama; Wiratama, Bayu Satria; Wulandari, Hanifah (BKM Public Health and Community Medicine, 2024)
Purpose: Mental disorders are the second leading global health burden among adolescents (15-19 years) and the third among adults (20-39 years). One approach to mitigate the medical and socio-economic impacts of mental disorders is the use of digital health technology, including chatbots. Methods: This study aimed to map mental health chatbot technology use through a scoping review. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extensions for Scoping Reviews (PRISMA-ScR) guidelines and involved PubMed, Scopus, ScienceDirect, and Google Scholar searches. The studies were categorized by type of usage, including acceptability, effectiveness, usability, adoption, and features. Study selection was assisted by Rayyan, and data extraction used a narrative approach. Results: Out of 172 research articles, 21 met the inclusion criteria and evaluated the use of mental health chatbots. Most chatbots were standalone applications (10/21). Adults (11/21) and university students (6/21) were the primary populations for testing chatbot usage. The most common mental health issues targeted by chatbots were anxiety, depression, and stress, although the focus was generally ideal for a range of mental health conditions. Conclusion: Numerous chatbots have been used for various mental health disorders, serving multiple purposes such as prevention, training, and therapy. Most applications combine these functions. Further research is needed to understand the changes that occur following mental health chatbot interventions.